Analisis Penyebab dan Jenis Kerusakan Rekam Medis Pasien Rawat Inap Akibat dari Keamanan Fisik, Kimia dan Biologi Pada Unit Filling di Rumah Sakit Umum Tabanan - Intan Pradani Asriningtyas Gunawan; Bambang Hadi Kartiko; I Wayan Nurata (Publikasi Indonesia, 2022)
According to observations made on data from December 2021 to January 2022 at RSU Tabanan Medical Record Installation, out of 300 inpatients' medical records, , the damage caused by physical factors amounted to 90 (30%), chemical factors amounted to 58 (19.3%) and biological factors amounted to 88 (29.3%). The aim of this study was to identify the physical, chemical, and biological sources and forms of damage to medical records. The research sample for this study consisted of 300 inpatient medical records, 1 head of the Medical Record Installation, 7 filling officers, and a qualitative-descriptive research methodology. The study's findings reveal the physical, chemical, and biological factors such as a cramped space and fully stocked medical record storage shelves, roof leaks that encourage mold growth, a humid environment, and the presence of rats, and cats that wander into the medical record storage room that lead to damage to inpatients' medical records. Medical record covers that are ripped, disconnected, and yellow to brown in color as a result of mildew and dust are three examples of medical record degradation caused by these three variables. Based on the study's findings, it can be said that physical, chemical, and biological variables cause damage to inpatients' medical records, with the forms of damage such as being torn, loose, and yellow to brown in color.